2023
DOI: 10.1136/bmjopen-2022-066841
|View full text |Cite
|
Sign up to set email alerts
|

IMPROVE-BMT: a protocol for a pilot randomised controlled trial of prehabilitation exercise for adult haematopoietic stem cell transplant recipients

Abstract: IntroductionHaematopoietic stem cell transplant (HSCT) in adults is an intensive medical procedure for a variety of haematological malignancies. Although there is a large body of evidence demonstrating the negative effects of HSCT on physical function and psychosocial parameters, there is limited evidence on the impact of HSCT on body composition and bone health. Further, aerobic and resistance-training exercise interventions aimed at improving physical function and patient-reported outcomes largely take place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Studies in adults have started to show the benefit of prehabilitation in cancer patients undergoing oncological surgeries, as well as HSCT. [12][13][14][15]17 Studies have shown improvement in fatigue, 6 MWT, and QOL in adult patients participating in exercise before, during, and after allogeneic HSCT. 29,30 Thus, it is logical to conclude that studying the effects of prehabilitation on preventing deconditioning in pediatric patients has the potential to provide benefits to these patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies in adults have started to show the benefit of prehabilitation in cancer patients undergoing oncological surgeries, as well as HSCT. [12][13][14][15]17 Studies have shown improvement in fatigue, 6 MWT, and QOL in adult patients participating in exercise before, during, and after allogeneic HSCT. 29,30 Thus, it is logical to conclude that studying the effects of prehabilitation on preventing deconditioning in pediatric patients has the potential to provide benefits to these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in adults have started to show the benefit of prehabilitation in cancer patients undergoing oncological surgeries, as well as HSCT 12–15,17 . Studies have shown improvement in fatigue, 6 MWT, and QOL in adult patients participating in exercise before, during, and after allogeneic HSCT 29,30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the feasibility of a multimodal prehabilitation is not yet well defined, especially among haematology patients treated with intensive chemotherapy and allo-HSCT. 56 Despite the promising results of prehabilitation before surgery, 57 the complexity of therapeutic trajectories in oncohaematology has so far made it difficult to set up prehabilitation interventions, as shown by the scarcity of studies over the last 10 years. The few recent studies of pre-HSCT prehabilitation are often unimodal, based on physical preparation alone.…”
Section: Introductionmentioning
confidence: 99%